Experiential Learning and Self-Efficacy in Physical Education of the Senior High School Students - Calubayan, John Carlo T.; Ofrin, Darwin O. (Future Science / FSH-PH Publications, 2023)
This study aimed to determine the level of involvement of senior high school students in experiential learning and also to determine of their described self-efficacy in physical education. This employed the research and descriptive correlation design of quantitative method as participated by three hundred fifty (350) senior high school respondents in San Isidro National High School who were chosen using purposive sampling procedures. The data were gathered using survey questionnaires which are validated with the help of the experts. Data communication was established before data gathering procedures and was analyzed using weighted mean, standard deviation, and Pearson’s r. Findings revealed that senior high school students agreed that they were involved in experiential learning. Students enhanced and boosted their self-efficacy through the use of mastery experiences, social modeling, social persuasions, and psychological responses. It was concluded that there’s a significant and strong positive correlation between experiential learning and students’ self-efficacy. It implied that as the students engage more in experiential learning, the higher the chance the students’ self-efficacy developed. Otherwise, the lesser engagement in experiential learning, the lower of chance developing self-efficacy. Based on the conclusion, it was recommended that the teachers are also recommended to motivate their students in involving experiential for them to mold and described their self-efficacy in engaging in physical activities.